2016
DOI: 10.3233/jvr-160822
|View full text |Cite
|
Sign up to set email alerts
|

Hiring of people with disabilities: Perceptions of Hispanic small business owners

Abstract: Abstract.BACKGROUND: Employment of people with disabilities continues to be a concern in the field of rehabilitation counseling. Employment rates remain low, resulting in many people with disabilities living at or below the poverty line. OBJECTIVE: The purpose of this study was to investigate the perceptions of Hispanic small business owners toward hiring people with disabilities. METHODS:The 38-item Employer Attitudes Questionnaire (EAQ) and the 33-item Small Business Owners Survey (SBOS) were used to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…These practices can help to minimize stigma and discrimination, while improving inclusion (Hernandez et al, 2008;Huang & Chen, 2015). An inclusive workplace environment refers to accepting and valuing diverse and under-represented groups such as persons with disabilities, women, and immigrants, and promotes integration in the workplace and in the community (Chen, Blankenship, Austin, Cantu, & Kotbungkair, 2016; Mor Barak, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These practices can help to minimize stigma and discrimination, while improving inclusion (Hernandez et al, 2008;Huang & Chen, 2015). An inclusive workplace environment refers to accepting and valuing diverse and under-represented groups such as persons with disabilities, women, and immigrants, and promotes integration in the workplace and in the community (Chen, Blankenship, Austin, Cantu, & Kotbungkair, 2016; Mor Barak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although most workplace accommodations can be provided at little or no cost (Dong, Oire, MacDonald-Wilson, & Fabian, 2013;Solovieva, Dowler, & Walls, 2011), less than one in five people with a disability receive accommodations in the workplace, and many people with disabilities are unprepared to disclose their condition or negotiate accommodations at work (Allen & Carlson, 2003;Brohan et al, 2012;Rumrill, Roessler, & Denny, 1997;Yelin, Sonneborn, & Trupin, 2000). Employers often lack knowledge of how to provide accommodations, and what accommodations they should provide to individuals with disabilities (Chen et al, 2016). A recent 2017 study showed that employers are more likely to grant workplace accommodations and see them as reasonable if employers are knowledgeable about disability legislation, have experience working with people with disabilities, and hold positive attitudes towards these individuals (Telwatte, Anglim, Wynton, & Moulding, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Kleynhans and Kotzé [ 41 ] studied the attitudes of co-workers towards people with physical disabilities and proved that contact with them, as well as knowledge, can have influence on shaping these attitudes. Chen et al [ 42 ], having studied Hispanic small business owners, concluded that the key factors determining employment included having a family member or friend with disability. The issue of perceiving people with disabilities by employers was also raised in [ 43 ], presenting a similar conclusion—positive attitudes are associated with greater experience with people with disabilities in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…However, when an employer has a negative attitude about people with disabilities, it is difficult for a person with a disability to be seriously considered for employment (Chen, Blankenship, Austin, Cantu, & Kotbungkair, 2016).…”
Section: Research On Employer Attitudesmentioning
confidence: 99%
“…This concern may be associated with lack of knowledge about both job accommodations and about visual impairment in general. A recent study found employers more concerned about hiring someone with a visual impairment than any other disability and those employers less willing to have a person with a visual impairment perform filing tasks than other job duties, indicating the employers had limited knowledge about job accommodations for people with visual impairments (Chen et al, 2016 (Crudden et al, 2002;. Developing ongoing relationships with employers is key to the dual customer or business relations approach to job development advocated by the Council of State Administrators of Vocational Rehabilitation, but little empirical research has been conducted that actually supports the efficacy of this approach.…”
Section: Employer Attitudes Toward People Who Are Blind or Visually Imentioning
confidence: 99%